2018
DOI: 10.1088/2058-6272/aad226
|View full text |Cite
|
Sign up to set email alerts
|

Electron density calculation based on Stark broadening of D Balmer line from detached plasma in EAST tungsten divertor

Abstract: Evidence and modeling of 3D divertor footprint induced by lower hybrid waves on EAST with tungsten divertor operations W. Feng, L. Wang, M. Rack et al. -A new experimental classification of divertor detachment in ASDEX Upgrade S. Potzel, M. Wischmeier, M. Bernert et al. -Inferring divertor plasma properties from hydrogen Balmer and Paschen series spectroscopy in JET-ILW B. AbstractThe electron density within the volume of the tungsten divertor of the Experimental Advanced Superconducting Tokamak (EAST) is calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…A detailed description of the multichannel visible spectroscopic diagnostic system for the upper divertor on EAST is given in [35]. The electron density in the upper divertor volume is calculated by a spectroscopic measurement of the Stark-broadened D ε line (396.90 nm) [36]. All the discharges discussed in this paper w ere set with the upper single null (USN) configuration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed description of the multichannel visible spectroscopic diagnostic system for the upper divertor on EAST is given in [35]. The electron density in the upper divertor volume is calculated by a spectroscopic measurement of the Stark-broadened D ε line (396.90 nm) [36]. All the discharges discussed in this paper w ere set with the upper single null (USN) configuration.…”
Section: Methodsmentioning
confidence: 99%
“…It is observed on EAST that Xpoint MARFE further evolved into wall MARFE. As shown in The electron density profiles in the divertor region are analyzed using the Stark broadening method [36]. As shown in figure 7, there are two density bands ; one is near the lines of sight passing through the strike point (first density band) and the other is near the X point (second density band).…”
Section: Wall Marfe On the High Field Sidementioning
confidence: 99%
“…Mao et al monitored the line radiation of W I to investigate the tungsten flux in the divertor of EAST [21]. By measuring the intensity ratio of C III and C IV, Koubiti et al obtained the electron temperature profile and showed the existence of a recombining zone around the X-point multifaceted asymmetric radiation from the edge (MARFE) in JT-60U [22]. Further, the high-resolution spectrometer of Alcator C-Mod was used to obtain the electron density by measuring the line shapes of the deuterium Balmer series [2].…”
Section: Introductionmentioning
confidence: 99%